Influence of social media influencers on adolescents’ confidence and emotions in health education - Nancy Sylvia Bawiling; Suprapto Suprapto (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: The growing popularity of social media has positioned influencers as important agents in shaping adolescents’ attitudes, behaviors, and perceptions toward reproductive health topics. Adolescence is a critical developmental period when understanding and confidence regarding reproductive issues are often limited. This study aimed to analyze the influence of exposure to influencer-generated content on adolescents’ positive emotions and self-confidence in the context of reproductive health education. Methods: A quantitative quasi-experimental design was employed, involving 100 students, divided equally into intervention and control groups. Data collection instruments included the Positive and Negative Affect Schedule (PANAS) to assess positive emotions and the Rosenberg Self-Esteem Scale to measure self-confidence. The intervention group received reproductive health education through influencer-created social media content, while the control group did not receive any exposure. Data were analyzed using the Paired Sample T-Test and the Independent T-Test. Results: The findings showed significant improvements in the intervention group across all variables: reproductive health knowledge (p=0.000), self-confidence (p=0.000), and positive emotions (p=0.000). In contrast, the control group exhibited no significant changes, indicating that influencer-based education effectively enhanced adolescents' cognitive and psychological aspects. Conclusion: Exposure to accurate, empathetic, relatable influencer content significantly improved adolescents’ emotional engagement and confidence. Therefore, collaboration among health educators, professionals, and social media influencers is recommended to develop credible, appealing, and youth-centered digital reproductive health communication strategies.